Censo visual como complementação metodológica em estudos ictiofaunisticos - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2023)
The Tocantins-Araguaia River Basin encompasses six Brazilian states and holds a rich ichthyofaunal diversity with high endemism. A project is planned to improve navigability of the waterway and enable year-round vessel traffic within the Tocantins-Araguaia drainage system. An environmental impact analysis was conducted to assess the socio-environmental feasibility of the process. However, concerning the ichthyofauna, many of the listed species do not effectively represent the diversity of fishes inhabiting the area, as numerous resident species have not been accurately cataloged. Therefore, effective and complementary methodologies are necessary to evaluate and diagnose the impacted rheophilic fish community, with the risk of neglect depending on the sampling method employed. This study aims to use visual census through diving as a complementary tool for inventorying rheophilic ichthyofauna in the Tocantins River in the Marabá region, near the well-known Pedral do Lourenço. In 2019, a 10-day expedition was conducted, averaging two dives per day during daylight hours, resulting in 105 minutes of footage. The results obtained were 5583 specimens from the 2017/2018 campaign by the Environmental Impact Study, 636 specimens collected during diving, and 143 individual fish records using visual census in 2019. The traditional methods captured a significant diversity of species (59.3%), but diving and visual census complemented this information by capturing exclusive and shared species. Characiformes were predominantly sampled through traditional methods (97.31%), while diving accounted for 13.52% and visual census for 9.79%. Siluriformes also exhibited differences in specimen capture, with diving and visual census playing important roles. The combination of these methods enhances efficiency in detecting fish diversity in rapids. The similarity between diving and visual census highlights their complementarity, as evidenced by the cluster analysis.
Keywords: Censo visua; Ictiofauna; Tocantins; Conservação; Reofílicos; Mergulho; Conservation; Rheophilic; Ichthyofauna; Diving; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA